Fisher consistent estimation of regression parameter in the proportional mean residual life model with frailty - Skolimowska-Kulig, Magdalena (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
In the article, we consider the Fisher consistent estimation of the regression parameters in the proportional mean residual life model with arbitrary frailty. It is discussed that conventional estimation procedures, such as the maximum likelihood estimation or Cox’s approach, which are employed incommon regression models, may also yield consistent inference in the extended models.
Keywords: proportional mean residual life regression model; frailty models; Fisher consistent estimation